d Factorize x 2 − y 2 − 4 x z + 4z 2 How to factorize ?

Question 4: Factorize x 2 − y 2 − 4 x z + 4z 2

Question 4: Factorize  x^{2}- y^{2}-4xz+4 z^{2}


How to factorize ?



To factorize this expression we first re-arrange terms as below

 x^{2}- y^{2}-4xz+4 z^{2}

so, we get ,  =x^{2}-4xz+4 z^{2}- y^{2}

Now brake second term as product of 2x and 2z as below

 =x^{2}-2(x)(2z)+4 z^{2}- y^{2}

Now first three terms are whole square expansion of  (x+2y) as you see below!

so we get , = (x+2z)^{2}- (y)^{2}

This is now a2-b2 form expression where a= x+2z-y and b= x+2z+y, so we get

= [x+2z-y][x+2z+y]





You may submit a MCQ or maths problem with solution tips here in the comment box below! If you could not solve anyone, you may submit a MCQ or maths problem without solution as well. We will try our level best to solve it for you!

Your email address will not be published.

You may use these <abbr title="HyperText Markup Language">HTML</abbr> tags and attributes: <a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>